Effects of crumb rubber on the frost resistance of cement-soil. (30th October 2019) - Wang, Fengchi; Ping, Xiaowei; Zhou, Jinghai; Kang, Tianbei
Highlights: The rubberized cement-soil with larger particle size has better frost resistance. The multiple corrosion and freeze-thaw cycles conditions are discussed. The mechanism of frost resistance of rubberized cement-soil is explained. Abstract: This study examines the effects of crumb rubber on the frost resistance of cement-soil. Rubber powder was incorporated into cement-soil (10%, 15%, 20% and 25%) at five different rubber contents (by weight) of 0, 5%, 10%, 15% and 20%. The main test included the early age frost test, the freeze-thaw cycle test, the corrosion-thaw-freeze cycle test and an SEM test, the results of which were analyzed to research the effect and mechanism of crumb rubber on the frost resistance of cement-soil. The growth rate of the compressive strength of the rubber cement-soil under a negative temperature is higher than that of cement-soil. The compressive strength of rubber cement-soil peaked between the 6th and 9th cycles and then decreased with an increase in the number of freeze-thaw cycles. Of the two particle sizes selected in the paper, 550 μm is better in terms of the frost resistance of the cement-soil. In the CTC experiment, the increase in the concentration of the sodium sulfate solution has less of an influence on the strength loss of rubber cement-soil than that of cement-soil. From the SEM test, it can be observed that the rubber particles hinder the development of frost heaving microcracks. All of the above tests show that rubber particles can effectively improve the frost resistance of cement-soil.